School absenteeism and self-efficacy in very-low-income students in Italy: Cross-lagged relationships and differential effects of immigrant background. (May 2022) - Bianchi, Dora; Cavicchiolo, Elisa; Manganelli, Sara; Lucidi, Fabio; Chirico, Andrea; Girelli, Laura; Cozzolino, Mauro; Alivernini, Fabio
Highlights: Self-efficacy and school absences were investigated in very-low-income students. Resistive self-efficacy and school absenteeism showed a bidirectional association. School absenteeism also lead to lower emotional self-efficacy over time. Low academic self-efficacy was a specific risk factor for immigrants (vs. natives) Abstract: School absenteeism is a serious problem among very-low-income students, with long-term consequences for well-being. Unfortunately, most acknowledged risk factors are difficult to modify through school-based interventions. However it is possible to hypothesize a link of school absenteeism with self-efficacy beliefs. The present two-wave study investigated the cross-lagged and bidirectional associations between school absenteeism and different domains of self-efficacy, among 242 very-low-income preadolescents and adolescents living in Italy ( Mage = 12.76; SDage = 2.37; 42.6% female; 19% immigrants; T1-T2 attrition rate of 18.8%; response rate of 79.1%). All participants were certified as living below the poverty line. Self-report questionnaires were administered in after-school educational centers for disadvantaged students. The results showed a bidirectional negative relationship between school absenteeism and resistive self-efficacy, and a negative relationship from school absenteeism to emotional self-efficacy. Moreover, academic self-efficacy turned out to be a negative predictor of school absenteeism only for immigrants. Implications for prevention, intervention, and future research are discussed.